Analysis of economic and financial indicators in agricultural enterprises (Zien Journal of Social Sciences and Humanities, 2024)
The economy of the agrarian sector plays an important role in ensuring the food security of each country and in the development of rural areas. This sector is necessary not only for food production, but also for economic stability and social development. Agricultural enterprises, in turn, actively participate in the processes of production, processing and distribution of agricultural products. This article provides detailed information about the analysis of economic and financial indicators, their importance and methods of analysis in agrarian enterprises